Brewers’ spent grain pretreatment optimisation to enhance enzymatic hydrolysis of whole slurry and resuspended pellet - Castilla-Archilla, Juan; Cermeño, Maria; Tuohy, Maria G.; FitzGerald, Richard J.; Lens, Piet N. L. (Frontiers in Chemical Engineering, 2023)
A thermal diluted acid pretreatment using brewers spent grain (BSG) was optimised to improve enzymatic hydrolysis while minimising energy and chemical inputs. First, the use of hydrochloric or sulfuric acid for pretreatment was compared, using hydrochloric acid for the next steps. Three different dilute acid thermal pretreatment combinations were optimised in terms of acid concentration, temperature and time using a response surface methodology. Optimization was based on i) highest remaining protein content in the solid fraction (C1: 0.49% HCl; 87.7°C; 92 min), ii) highest liquid recovery (C2: 0.80% HCl; 121.0°C; 142 min), iii) lowest acid concentration applied to achieve largest protein and lowest remaining solid levels (C3: 0.10% HCl; 104.0°C; 70 min); and iv) a final condition based on the lowest water retention capacity when using HCl (C4: 0.20% HCl; 121.0°C; 20 min). The efficiency of enzymatic hydrolysis was evaluated, in the absence and presence of a large concentration of reducing carbohydrates, by centrifuging the slurry after acid pretreatment, recovering the solid fraction and resuspending it in fresh water. In C2, the enzyme (Depol 40L) was added directly to the entire slurry after pretreatment. For C1, C3 and C4 direct addition of enzyme to the whole slurry resulted in a higher release of carbohydrates during hydrolysis. Only in the case of C2 did the use of the resuspended solid result in a higher carbohydrate release. The overall carbohydrate recovery efficiency in the liquid fractions for C1, C2, C3 and C4 corresponded to 399.1 (± 26.1), 535.8 (± 28.7), 257.0 (± 11.5) and 446.3 (± 81.1) mg carbohydrate per gram of BSG (dry weight), respectively. C1 and C4 were considered the optimal pretreatments as these combined a low acid concentration and energy input prior to enzymatic hydrolysis.